MORPHOLOGICAL AND THERMAL PROPERTIES STUDY OF PCL BIOCOMPOSITES WITH NANOCELLULOSE FILLER FROM RICE HUSK USING PCLacac COMPATIBILIZER AS MATERIAL CANDIDATE FOR BONE SCAFFOLDS - Muhammad Yusuf; Yossie Juliastri Napitupulu; Eddiyanto Eddiyanto; Innayah Wulandari; Winsyahputra Ritonga (EINSTEIN (e-Journal), 2026)
Biocomposites from poly(ε-caprolactone) (PCL) matrix with nanocellulose filler are materials that have been developed for biomedical applications, such as scaffolds, tissue engineering, implants, and wound dressings. The PCL matrix is flexible and biocompatible. Meanwhile, the rice husk nanocellulose filler is environmentally friendly, renewable, and abundantly available in Indonesia. However, the differences in the hydrophobic properties of PCL and the hydrophilic properties of nanocellulose cause low interfacial adhesion, so a compatibilizer is needed to improve the compatibility of the two phases. This study aims to examine the effect of adding short-chain PCL (PCLacac) as a compatibilizer. The mixing of the PCL matrix, nanocellulose filler, and PCLacac compatibilizer used the solvent casting method. The characterization results using Scanning Electron Microscopy (SEM) showed that the addition of PCLacac can improve interfacial adhesion between the matrix and filler, characterized by a more even filler dispersion and reduced agglomeration. On the other hand, thermogravimetric analysis (TGA) analysis showed that the addition of 3% PCLacac resulted in an increase in decomposition temperature, which indicates an increase in thermal stability due to better interfacial interactions between the matrix and filler. Thus, the addition of PCLacac plays an effective role in improving the morphological structure and thermal resistance of PCL/rice husk nanocellulose biocomposite, so it has the potential to be developed as a biocomposite material in biomedical applications including bone scaffolds.